"I Might as Well Get My Education": The Experiences of Black Male Division III College Athletes - Lisa Rubin; Rhema Fuller; Sarah Stokowski (Bowling Green State University, 2022)
Division III college athletes have been largely ignored in the growing literature involving college sport. Given that the majority of college athletes that participate in high profile sports are athletes of color, there is a need to explore the experiences of this population, specifically at the Division III level. Informed by the Excellence Beyond Athletics (EBA) framework, which empowers students of color, especially Black male athletes, the purpose of this study is to explore the experiences of Black male athletes at two rural Division III institutions. Ten Black male Division III athletes took part in semi-structured interviews. Using inductive analysis and descriptive coding, six final themes were established: College Choice/Financial Issues, Academics, Time Management, Athletic Identity/Culture, Commitment to Athletics, and Campus Climate/Black Experience. This study strives to better understand the experiences of Black male college athletes at the Division III level in hopes of enhancing the student experience through impactful programming.